Bionic Design for Mars Sampling Scoop Inspired by Himalayan Marmot Claw. (29th December 2016) - Xue, Long; Zhang, Rong Rong; Zong, Wei; Song, Jia Feng; Zou, Meng
Abstract : Cave animals are often adapted to digging and life underground, with claw toes similar in structure and function to a sampling scoop. In this paper, the clawed toes of the Himalayan marmot were selected as a biological prototype for bionic research. Based on geometric parameter optimization of the clawed toes, a bionic sampling scoop for use on Mars was designed. Using a 3D laser scanner, the point cloud data of the second front claw toe was acquired. Parametric equations and contour curves for the claw were then built with cubic polynomial fitting. We obtained 18 characteristic curve equations for the internal and external contours of the claw. A bionic sampling scoop was designed according to the structural parameters of Curiosity 's sampling shovel and the contours of the Himalayan marmot's claw. Verifying test results showed that when the penetration angle was 45° and the sampling speed was 0.33 r/min, the bionic sampling scoops' resistance torque was 49.6% less than that of the prototype sampling scoop. When the penetration angle was 60° and the sampling speed was 0.22 r/min, the resistance torque of the bionic sampling scoop was 28.8% lower than that of the prototype sampling scoop.